Observational Properties of 15MLT‐PCA in the Southern Hemisphere and the Switching Effects of IMF By on 15MLT‐PCA Occurrence. Issue 12 (10th December 2021) - Feng, Hui‐Ting; Han, De‐Sheng; Qiu, Hui‐Xuan; Shi, Run; Yang, Hui‐Gen; Zhang, Y.‐L.
Abstract: Based on Special Sensor Ultraviolet Spectrographic Imager on Defense Meteorological Satellite Program spacecraft (DMSP/SSUSI) observations in the Northern Hemisphere, a particular polar cap arc observed at ∼1, 500 magnetic local time (MLT) sector was identified and was named 15MLT‐PCA. A 15MLT‐PCA model proposed for the Northern Hemisphere suggests that the 15MLT‐PCA is caused by a lobe reconnection related to the tilt angle and lobe field line twisting due to a long‐lasting positive interplanetary magnetic field (IMF) By condition. However, it is unclear if the 15MLT‐PCA can be observed in the Southern Hemisphere and how the IMF By influences its occurrence and location. Using the long‐term DMSP/SSUSI observations in the Southern Hemisphere, we confirmed that the 15MLT‐PCA could be observed in the Southern Hemisphere in summer under long‐lasting negative IMF By and predominantly positive IMF Bx . The ion energy dispersion and some other statistical properties are also investigated. Further, we showed that the IMF By has a switching effect on the occurrence of the 15MLT‐PCA using multiple cases. We found that the 15MLT‐PCA disappear as soon as the IMF By changed to an unfavorable condition, but it seems that the favorable conditions need to be maintained for ∼1 hr for the occurrence of 15MLT‐PCA. We also found that the IMF By magnitude is well correlated to the MLT location of the 15MLT‐PCA. We suggest that all the results support the 15MLT‐PCA model and imply that a magnetotail lobe reconnection should be common in the summer hemisphere because the well‐known Parker Spiral favors meeting the model's IMF requirements. Plain Language Summary: It is well known that the interplanetary magnetic field (IMF) is in a Parker Spiral pattern, so in quiet solar conditions, a stable IMF By component can often be observed around 1 AU. At the same time, the geomagnetic dipole axis tilts with the ecliptic plane at different angles under different seasons and Universal Time (UT). What the combined effect of stable IMF By and dipole tilting is is unknown. A recent model of 15MLT‐PCA (polar cap arc at ∼1, 500 MLT sector) suggests that the stable IMF By and dipole tilting can lead to a particular lobe reconnection. This model may reveal an important geophysical process. However, its validation is still needed because it was proposed based on merely northern‐hemisphere observations. In this study, we carefully examined the properties of 15MLT‐PCA based on southern‐hemisphere observations. The results are well consistent with the model's predictions and thus provide support to the model. Key Points: Statistical properties of 15MLT‐PCA in the Southern Hemisphere are confirmed to be consistent with a previously proposed 15MLT‐PCA model The interplanetary magnetic field By shows a clear switching effect on the occurrence of 15MLT‐PCA and affects its MLT location 15MLT‐PCA was not observed immediately when favorable IMF conditions appeared, but after the conditions were maintained for ∼1 hr